ANALISIS USAHA DAN STRATEGI PENGEMBANGAN TERNAK KALKUN MITRA ALAM KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Rizky, Adelia; Haryono, Dwi; Kasymir, Eka (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This research aims to analyze business activities and strategic development of Mitra Alam turkey farming Pringsewu Districtof Lampung Province. This research method is a case study, using descriptive data analysis by applying the formulation of economic evaluations which arerevenue, Break Even Point (BEP), R/C ratio and SWOT analysis. These results indicate that turkey farm of Mitra Alam is potential to be developed. The position of Mitra Alamturkey farm is in quadrant II which belongs to diversification area. The priorities strategic for Mitra Alamturkey farm are development of quality product by following the coach and business training to develop turkey breeding in other places, using advanced technologies to increase the quality and quantity according to the preference of people on consumeing high nutritious product, hire a professional animal husbandry to keep the quality, so people know the benefits of Key words: strategic development, SWOT analysis, turkey farm